2022
DOI: 10.3390/s22218128
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Motor Imagery Detection System Using Electroencephalography with Adaptive Wavelets

Abstract: Classification of motor imagery (MI) tasks provides a robust solution for specially-abled people to connect with the milieu for brain-computer interface. Precise selection of uniform tuning parameters of tunable Q wavelet transform (TQWT) for electroencephalography (EEG) signals is arduous. Therefore, this paper proposes robust TQWT for automatically selecting optimum tuning parameters to decompose non-stationary EEG signals accurately. Three evolutionary optimization algorithms are explored for automating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…The method involves using the TQWT technique with automatically selected tuning parameters and then selecting important features from the resulting signals using a least squares SVM classifier. The proposed method achieved high accuracy of 99.78%, which is superior to other state-of-the-art techniques using the same database [61]. Maksimenko et al found that a combination of delta and mu/alpha frequency bands in EEG signals can be used to extract features of brain activity associated with motor execution and MI in untrained individuals.…”
Section: Nonlinear Dynamical Studies On Motor-imagerymentioning
confidence: 95%
“…The method involves using the TQWT technique with automatically selected tuning parameters and then selecting important features from the resulting signals using a least squares SVM classifier. The proposed method achieved high accuracy of 99.78%, which is superior to other state-of-the-art techniques using the same database [61]. Maksimenko et al found that a combination of delta and mu/alpha frequency bands in EEG signals can be used to extract features of brain activity associated with motor execution and MI in untrained individuals.…”
Section: Nonlinear Dynamical Studies On Motor-imagerymentioning
confidence: 95%
“…Among BCI modalities, electroencephalography (EEG) is frequently used because of its high temporal resolution, noninvasiveness, and portability. EEG signals have shown an excellent ability to classify different motor conditions [ 5 ] and different motions during MI tasks [ 6 , 7 ]. In the former studies of EEG, many investigations have been focused on static features, which may lose important temporal information.…”
Section: Introductionmentioning
confidence: 99%
“…Similar attempts have been made in the study of EEG (electroencephalogram) signals since there are many diferent waves in the EEG (mainly consisting of α, β, c, δ,, and θ), and the application of EEG signals to solve some practical problems requires the analysis of diferent waves: the literature [22] developed a scheme to automatically identify schizophrenia by decomposing the EEG signal through EMD (empirical mode decomposition) and calculating 22 each feature from it; Reference [23] proposed a computer-aided clinical decision support system (CACDSS) to detect and diagnose Parkinson's disease through EEG by combining automatic variational modal decomposition (AOVMD) and automatic extreme learning machine (AOELM) classifers; the literature [24] developed an EEG rhythm separation (VHERS) based on variational modal decomposition (VMD) and Hilbert transform (HT) to help experts detect attention defcit hyperactivity disorder (ADHD) in a real-time situation. Reference [25] proposed the robust tuneable Q wavelet transform (TQWT) for the automatic selection of optimal tuning parameters to accurately decompose nonsmooth EEG signals and identify motor imagery (MI) tasks with low complexity.…”
Section: Introductionmentioning
confidence: 99%